The Effect of Radiation on MHD Natural Convection Flow of Fluid with Variable Viscosity from a Porous Vertical Plate - Ferdousi, Amena; Rahman, M. Mostafizur; Parvez, Mohammad Salek; Alim, M. A. (International Journal of Advanced Mathematical Sciences, 2013)
This paper presents a new extension for the effect of Radiation on MHD Natural Convection Flow with Variable Viscosity from a Porous Vertical Plate. The governing  boundary layer equations are first transformed into a non dimensional form and the resulting non linear system of partial differential equations are then solved numerically using finite difference method together with Keller-Box scheme. The numerical results show that the variable viscosity affects the surface shear stress and the rate of heat transfer which are here in terms of skin friction coefficient and local Nusselt number. It affects velocity as well as temperature profiles also. These are shown graphically and tabular form for a selection of parameters set of consisting of viscosity variation parameter g, magnetohydrodynamic parameter M, radiation effect Rd, Prandtl number Pr.